Analysis of external morphological characters of selected species of babblers (Family : Timaliidae) in determining sexual dimorphism - Sitty Nurhamiza, Binti Mohd Hamdan (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Babblers (Family Timaliidae) are distinguished by their ranges in size from nine to 41 cm, while their colours vary from the plain browns and grays. They are distributed nearly in all tropical or subtropical areas. In this study, only 18 species of babblers have been examined. Eight morphological features; tail anus , tarsus, bill and wings were measured from 444 specimens of 18 babblers species of Borneo available in the Sarawak Museum collections. The specimens were analyzed using the morphometric cluster analysis, discriminant function analysis, and also logistic regression analysis. Results show that only 13 species can be distinguished between males and females based on logistic regression analysis. For cluster analysis, nine species represents nine genera were grouped in five. As for discriminant function analysis, they were grouped in four. Based on the results, Babblers species were determined to be strongly monomorphic bird, as it is quite hard to distinguish them based on the morphological characteristics. Overall, it is recognized that males are usually larger than females.